2020
DOI: 10.18632/aging.103553
|View full text |Cite
|
Sign up to set email alerts
|

A new survival model based on ferroptosis-related genes for prognostic prediction in clear cell renal cell carcinoma

Abstract: In this study, we analyzed the clinical significance of ferroptosis-related genes (FRGs) in 32 cancer types in the GSCA database. We detected a 2-82% mutation rate among 36 FRGs. In clear cell renal cell carcinoma (ccRCC; n=539) tissues from the The Cancer Genome Atlas database, 30 of 36 FRGs were differentially expressed (up- or down-regulated) compared to normal kidney tissues (n=72). Consensus clustering analysis identified two clusters of FRGs based on similar co-expression in ccRCC tissues. We then used L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 30 publications
5
74
0
Order By: Relevance
“…Recently, we found three studies that have reported ferroptosis gene signatures. These three studies focused on HCC [54], clear cell renal cell carcinoma [55], and glioma [56]. There are some similarities between our research and these three articles.…”
Section: Discussionmentioning
confidence: 60%
“…Recently, we found three studies that have reported ferroptosis gene signatures. These three studies focused on HCC [54], clear cell renal cell carcinoma [55], and glioma [56]. There are some similarities between our research and these three articles.…”
Section: Discussionmentioning
confidence: 60%
“…Recently, we found three studies that have reported ferroptosis gene signatures. These three studies focused on HCC [50], clear cell renal cell carcinoma [51], and glioma [52]. There are some similarities between our research and these three articles.…”
Section: Discussionmentioning
confidence: 63%
“…ATP5MC3, also named ATP5G3 [39], encoding a subunit of mitochondrial ATP synthase, was associated with overall survival in clear cell renal carcinoma patients [40]. CARS1, Cysteinyl-TRNA Synthetase 1, associated with tRNA function, has been found associated with the development of inflammatory myofibroblastic tumor [41] and kidney cancer [42].…”
Section: Discussionmentioning
confidence: 99%